Immunmilk® Feeding Increases Growth and Immune Responses in Broiler Chicks - Qureshi, M.A.; Ali, R.; Cheema, M.A.; Ahmed, Z.; Roth, H. (International Journal of Poultry Science, 2004)
A study was conducted to measure baseline immunocompetence of Arbor Acre broiler chicks after the birds were raised on hyperimmune bovine colostrum product ‘Immunmilk®` for first 7 d of age. Immunological parameters measured were in vivo and in vitro lymphoproliferation, macrophage functions which included phagocytosis, nitric oxide production and E. coli clearance from circulation; and antibody response against SRBC. In addition, body weights (BW) and lymphoid organ weights were also determined. Immunmilk®-treated chicks exhibited significantly higher BW at 7 (18.1% heavier) and 13 d (26% heavier) of age when compared with the chickens in control group. In vitro lymphoproliferative response of blood leukocytes to Concanavalin-A was increased (P = 0.0024) while in vivo lymphoproliferation to Phytohemagglutinin-P was down-regulated (P ≤ 0.01) in Immunmilk®-treated group. Macrophage phagocytic potential against SRBC was significantly higher and nitric oxide production was reduced in macrophages from Immunmilk® treated chicks. Systemic E. coli clearance after i.v. challenge was much more rapid in Immunmilk®-treated chicks. Immunmilk® treatment also increased total and IgM anti-SRBC antibody levels (P ≤ 0.05) during secondary antibody response. The results of this study showed that Immunmilk® increased growth as well as immune performance of chickens as measured by humoral (antibody) response, mononuclear phagocytic system function as well as lymphoproliferation. However, inflammatory processes such as in vivo mitogen-induced T-lymphocyte proliferation and LPS-mediated nitric oxide production by macrophages were down regulated.